2006
DOI: 10.1504/ijaape.2006.010102
|View full text |Cite
|
Sign up to set email alerts
|

The extent of financial disclosure and its determinants in an emerging capital market: the case of Egypt

Abstract: This paper uses panel data to investigate the extent and determinants of disclosure levels of non-financial companies quoted on the Egyptian Stock Exchange.Results show gradual increases in disclosure levels, with a high compliance for mandatory disclosure, although the voluntary disclosure level was rather limited.Public sector companies appear generally to disclose less information than private sector companies in terms of the layout of the balance sheet, cash flow statement, notes to accounts, policies adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 8 publications
8
86
2
5
Order By: Relevance
“…No significant correlation is observed between either credit risk, interest rate risk or/and their total with total assets and market capitalization for either years (2005 and 2008). This result goes against earlier studies (for example, Botossan, 1997;Ahmed and Courtis, 1999;Street and Bryant, 2000;Camfferman and Cook, 2002;Ali, Ahmed, & Henry, 2004;Al Saeed, 2006;Hassan, et al 2006;and Mangena et al 2007) which support that a size-disclosure relationship does exist. Furthermore, Woods et al (2009) also discovered in their research that there is no association among the bank size and the quantity of disclosures.…”
Section: Hypotheses Testingcontrasting
confidence: 77%
“…No significant correlation is observed between either credit risk, interest rate risk or/and their total with total assets and market capitalization for either years (2005 and 2008). This result goes against earlier studies (for example, Botossan, 1997;Ahmed and Courtis, 1999;Street and Bryant, 2000;Camfferman and Cook, 2002;Ali, Ahmed, & Henry, 2004;Al Saeed, 2006;Hassan, et al 2006;and Mangena et al 2007) which support that a size-disclosure relationship does exist. Furthermore, Woods et al (2009) also discovered in their research that there is no association among the bank size and the quantity of disclosures.…”
Section: Hypotheses Testingcontrasting
confidence: 77%
“…Additionally, the present study addresses the call for further research in the field of mandatory disclosures (Leuz & Wysocki, 2008;Schipper, 2007 Hassan et al (2006) argue that one of the reasons that little attention has been given to mandatory disclosures is that most studies are conducted in developed markets with strong enforcement mechanisms, which ensure a high level of compliance with mandatory disclosures by almost all companies. Nevertheless, there is evidence that the excessive disclosure requirements mandated by IFRS are not fully followed in even some of the most developed markets.…”
Section: H1: Purchased Goodwill Under Ifrs Is Value Relevantmentioning
confidence: 97%
“…Notably, a stream of empirical research has found that larger companies are more inclined to disclose greater amount of disclosure (Wallace et al, 1994;Beattie et al, 2004;Hassan et al, 2006;Alsaeed, 2006) and to follow better disclosure practices (Ahmed & Courtis, 1999). In particular, empirical findings from previous studies demonstrated that total level of forward-looking information is positively related with company size (Walker & Tsalta, 2001;Kent & Ung, 2003;Vanstraelen et al, 2003;Leventis & Weetman, 2004;Gao et al, 2005;Hossain et al, 2005;Celik et al, 2006;Celik et al, 2006;Lim et al, 2007;Hossain & Hammami, 2009;Abed et al, 2011).…”
Section: Firm Sizementioning
confidence: 99%
“…There are several reasons for such a positive relationship. For instance Hassan et al (2006) argued that large companies might have a lot of resources to sustain additional information costs if they provide more relevant disclosure to different users.…”
Section: Firm Sizementioning
confidence: 99%